2009
DOI: 10.1055/s-0029-1211419
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of hypothalamic-pituitary-adrenal system response to a combined dexamethasone-CRH test in multiple sclerosis

Abstract: The endocrine system participates in the regulation of the immune and neural systems and therefore hormonal factors probably play an important role in the development and course of multiple sclerosis (MS). Specifically, the hypothalamic-pituitary-adrenal (HPA) system seems crucial because (a) the inflammatory response is accompanied by HPA activation; (b) animal models with an inherited HPA defect are prone to developing experimental autoimmune encephalitis; and (c) most important, corticosteroids are still th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Elevated levels of ACTH and cortisol in response to CRH administration in MS patients have frequently been reported [13], [14], [26] and endocrine changes seem to be associated with clinical course as well as disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated levels of ACTH and cortisol in response to CRH administration in MS patients have frequently been reported [13], [14], [26] and endocrine changes seem to be associated with clinical course as well as disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…In response to intravenous administration of CRH, cortisol release was increased in MS patients compared to healthy control subjects [12], [13]. HPA axis function also seems to be linked to radiological as well as clinical aspects: increased cortisol response to CRH was associated with gadolinium enhancing lesions, a marker for acute central nervous system inflammation in MS [14].…”
Section: Introductionmentioning
confidence: 99%
“…Because cortisol, like exogenously administered glucocorticoids, attenuates the immune response, such an endocrine effect might contribute to the therapeutic actions of IFN‐β in multiple sclerosis. Several groups have found disturbances of the hypothalamo‐pituitary‐adrenal (HPA) axis in multiple sclerosis, 7–14 suggesting that the neuroendocrine responses to IFN‐β may be altered or heterogeneous. If such responses were associated with varying therapeutic effects, they could be useful to predict benefit of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Using the more sensitive combined dexamethasone-corticotropin releasing hormone (CRH) test, Grasser et al found a normal ACTH response but a higher mean plasma cortisol response in 19 MS patients in acute relapse compared to age-matched controls. Six of the 19 had an excessive release of cortisol; four did not respond at all [89]. Wei and Lightman studied 21 patients with definite MS, most within 1 month of clinical relapse [227].…”
Section: The Hypothalamic Pituitary Adrenal Axis Function In Eae and Msmentioning
confidence: 99%